Post-acute surgical ward round proforma improves documentation. Issue 1 (17th May 2013) - Al-Mahrouqi, Haitham; Oumer, Ramadan; Tapper, Richard; Roberts, Ross
Abstract: In health care, record keeping of doctor-patient encounters is vital for quality patient care and medico-legal reasons. We audited the documentation of post-acute consultant ward round (PACWR) in our department before and six months after an introduction of a proforma (standard form). The clinical notes of all patients admitted acutely under General Surgery over a period of one week before and one week after the introduction of a proforma were reviewed to note whether time and date, signature, impression and dietary plan were documented after PACWR. The nurses were also surveyed on the day of the PACWR for their certainty regarding the dietary plan of their patients and whether they had to contact the surgical team for clarification. There were 108 and 103 patients eligible for the first and second study periods respectively. After the introduction of the proforma, there was a statistically significant improvement in the documentation of time and date (37% vs. 72%, p-value <0.01) and impression (40% vs. 61%, p-value <0.01). Improvement in the documentation of the dietary plan reached statistical significant only when the analysis was restricted to the cases where a proforma was filled out (78 out of 103 patients). Introduction of the proforma had no statistically significant impact on the nurses' certainty regarding their patients' dietary plan and the number of times they had to contact the surgical teams. In conclusion, PACWR proforma improves overall documentation. This will help in avoiding adverse effects on patient care and medico-legal ramifications.